GESTATION AGREEMENT. AN ANALYSIS FROM THEMEXICAN EXPERIENCE - Guzmán-Ávalos, Aníbal (2022)
In this work, an analysis is made based on the agreements on gestation on which a woman who is sorted as pregnant is forced with another or other people to follow a physiological procedure in a child’s gestation to enable her maternity and/or paternity, which from a variaty of reasons cannot be achieved themselves, by which they are compromised to do everything that is needed to achieve reproduction. This fact engenders a series of legal effects that are being tried to be identified and set in the property right’s field. Independently either it is about enforcing a right in the autonomy willing ambit in the matter of family relationships. Therefore, the decision to agree on procreation of a child is in the sphere of a family right wise context, constitutionally recognized but outsourced under the vision of the patrimonial law in a lato sensu agreement. Therefore, the elements of the agreement are analyzed so that it has existence and validity, pointing out in any case, its ineffectiveness and legal responsibility in the law matters in Mexico.